THE IMPORTANCE OF MECHANIZATION IN THE DEVELOPMENT OF AGRICULTURE IN THE FERGANA VALLEY - Umida Maripjanovna, Akhmedova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study investigates the role of mechanization in transforming agriculture in Uzbekistan’s Fergana Valley following independence. Method: An evaluative analysis was conducted on the integration of modern agricultural technologies with high-performance mechanical farming equipment to assess impacts on productivity, resource management, yield production, land optimization, and labor cost reduction. Results: The findings reveal a marked shift in agricultural practices in the region, driven by the adoption of advanced machinery and innovative techniques that have significantly enhanced operational efficiency and resource allocation. Novelty: The research underscores the unique governmental emphasis on agricultural mechanization as a cornerstone of national development, offering novel insights into the multifaceted benefits and challenges associated with technological progress in agricultural production. This study significantly contributes to the existing literature by elucidating the dynamic interplay between technology adoption and agricultural reforms, thereby providing a comprehensive framework for understanding mechanization as a pivotal factor in driving rural development and economic growth in post-independence Uzbekistan.